2009
DOI: 10.1002/ana.21916
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to native myelin oligodendrocyte glycoprotein in children with inflammatory demyelinating central nervous system disease

Abstract: Overall, these findings suggest nMOG as a major target of the humoral immune response in a subgroup of children affected by inflammatory demyelinating diseases of the CNS. Children may provide valuable insight into the earliest immune mechanisms of CNS demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
247
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(257 citation statements)
references
References 37 publications
8
247
1
1
Order By: Relevance
“…Similarly, MS lesions may show local deposition of immunoglobulins and activated complement at sites of active demyelination, but also this is only seen in a subset of patients [73]. Autoantibodies, directed against the target epitope of myelin oligodendrocyte glycoprotein, which is recognized in the process of demyelination, have been detected in a small subset of MS patients, which mainly consists of children with atypical disease course [13]. Other molecular targets for demyelinating antibodies are glycolipids, but their pathogenic potential in inflammatory demyelinating lesions is less clear.…”
Section: Demyelination and Neurodegenerationmentioning
confidence: 99%
“…Similarly, MS lesions may show local deposition of immunoglobulins and activated complement at sites of active demyelination, but also this is only seen in a subset of patients [73]. Autoantibodies, directed against the target epitope of myelin oligodendrocyte glycoprotein, which is recognized in the process of demyelination, have been detected in a small subset of MS patients, which mainly consists of children with atypical disease course [13]. Other molecular targets for demyelinating antibodies are glycolipids, but their pathogenic potential in inflammatory demyelinating lesions is less clear.…”
Section: Demyelination and Neurodegenerationmentioning
confidence: 99%
“…Detection of MOG antibodies may help to differentiate autoimmune and infectious CNS disease and may give prognostic information regarding monophasic or recurrent course. 1 Brilot et al 6 reported that 40% of children with ADEM in their study had high anti-MOG IgG titers. The antibody response against MOG was primarily of the IgG isotype and anti-MOG IgM was rarely found.…”
Section: Figurementioning
confidence: 86%
“…Recent studies proposed that myelin basic protein, myelin proteolipid protein, myelin-associated glycoprotein, and MOG are the targets of the immune system in demyelinating diseases. 2,6 MOG is a candidate target antigen in demyelinating CNS diseases. It is e4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high proportion of patients with ADEM, especially children, are found to have antibodies directed toward myelin oligodendrocytes glycoprotein [63][64][65][66]. AHLE has been reported to occur in the context of several different viral infections, including cytomegalovirus, Epstein Barr virus, herpes simplex virus, the mumps virus, and the H1N1 virus [67][68][69][70][71].…”
Section: Ademmentioning
confidence: 99%